A Study on the Development of Functionally Improved Low Fat Spent Broiler Breeder Hen Chicken Sausages Added with Ground Poppy Seed - Indumathi, J.; Shashikumar, M.; Reddy, G. Vijaya Bhaskar; Babu, A. Jagadeesh; Prakash, M. Gnana (International Journal of Livestock Research, 2021)
Spent broiler breeder hen meat was utilized for development of low-fat functional chicken sausages fortified with ground poppy seed at three different levels (5, 7.5 and 10%) as partial chicken fat replacer to select optimum level of incorporation based on physico- chemical, proximate, fatty acid composition and sensory evaluation. Low fat chicken sausages incorporated with ground poppy seed at 10 % level were found to have significantly (P<0.05) higher pH, cooking yield, emulsion stability, hardness, crude protein, crude fiber, total ash, PUFA /SFA ratio, mono and poly unsaturated fatty acids and significantly lower moisture, crude fat, cholesterol and saturated fatty acids when compared to the control and rest of the poppy seed fortified sausages with no significant difference was observed in sensory scores.